'89, the unfinished revolution power and powerlessness in Eastern Europe - Thorpe, Nick (Reportage, 2009)
"BBC journalist Nick Thorpe has witnessed first-hand some of the most tumultuous events of the past twenty-five years in eastern Europe: the Velvet Revolution in Prague; the bloody uprising in Romania; the bombing of Belgrade; and the economic crash of 2008. But for Thorpe the revolutions of 1989 roll on, yet to reach their conclusions. The old cold war has been replaced by a new cold war - this time between the people and the state. In '89: The Unfinished Revolution Nick Thorpe weaves the political with the personal, anecdote with analysis, to produce an energising and important account of history in the making." --Book Jacket